First record of Arctotherium (Ursidae, Tremarctinae) in northwestern Argentina: paleobiogeographic significance. - Garcia Lopez, Daniel Alfredo (2008)
Here we describe the first remains of Arctotherium from Late Pleistocene deposits of Catamarca Province, northwestern Argentina. This material narrows the geographical gap between two previously known fossiliferous localities separated by more than 1200 km. Institutional Abbreviations—BMNH, Natural History Museum, United Kingdom; GP, Museu Paulista, Universidade de Sâo Paulo, Brazil; MACN, Museo Argentino de Ciencias Naturales ‘Bernardino Rivadavia’, Buenos Aires, Argentina; MMMP, Museo Municipal de Mar del Plata ‘Lorenzo Scaglia’, Argentina; PVL, Colección Paleontología de Vertebrados Lillo, Tucumán, Argentina; UZM, Zoological Museum, University of Copenhagen, Denmark.